The long road to cooperation and integration across Africa - Jaime De Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2025)
Ever since their independence, African countries have engaged in a series of treaties creating 8 Regional Economic Communities (RECs) that were (and still are) to pilot this integration starting with a Free Trade Area (FTA) followed by a customs union, a common market, and a monetary union following a 'variable geometry', along a 'Minimum Integration Program' at different speeds. This introductory chapter summarizes takeaways from the essays collected in the booklet Essays on Africa's Integration: Prospects and Challenges for Markets and Regional Public Goods.
Keywords: 330; Regional integration